Performance of Kenaf geotextile in improving bearing capacity of soft soil - Mohammad Gharehzadeh Shirazi, 1983-, author; Ahmad Safuan A. Rashid, supervisor; Ramli Nazir, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2019